Knowing the subject matter of a secondary‐school science subject - Deng, Zongyi (Journal of Curriculum Studies, 2007)
This paper examines the fundamental yet largely neglected distinction between school subjects and academic disciplines in the discourse on teachers’ specialized subject‐matter knowledge. It analyses and critiques the curricular positions embedded in that discourse in the light of five possible relationships between school subjects and academic disciplines. Invoking Dewey’s logical‐psychological distinction and research findings, the paper argues that the subject matter of a secondary‐school science subject instead of the subject matter of its parent academic discipline lies at the heart of secondary‐school science teachers’ specialized subject‐matter knowledge. Knowing such subject matter entails knowing five intersecting dimensions: the logical, the psychological, the pedagogical, the epistemological, and the sociocultural. Implications are drawn concerning theorizing about what secondary‐school science teachers need to know about the subject matter they are expected to teach, subject‐matter preparation for teaching, and the development of secondary‐school science curriculum materials.